BUILDING KNOWLEDGE-SHARING PRACTICES FROM AN ENTREPRENEURIAL ORIENTATION : THE MODERATION ROLE OF DIGITALIZATION AND RELIGIOSITY : - - Eduard Alfian Syamsya Sijabat (Asosiasi Dosen Muda Indonesia, 2025)
Knowledge-sharing practices are needed as a tool for improving the company's performance capabilities. Knowledge-sharing practices are correlated with the existence of entrepreneurial orientation, which manifests in proactive orientation, innovative orientation, and risk-taking orientation. In addition, digitalization and religiosity factors are suspected of influencing knowledge-sharing practices. This study aimed to explore knowledge-sharing practices that can be generated from entrepreneurial orientation moderated by digitalization factors and also religiosity factors possessed by human resources in shipping agency service companies in Indonesia. This study used the object of research of shipping agencies companies in Indonesia and the results were analyzed using structural equentional model (SEM) WarPls 7. The results of the study showed that entrepreneurial orientation has a significant effect on knowledge-sharing practices. The implementation of digitalization in companies, the results of the study showed that digitalization significantly strengthens the influence of entrepreneurial orientation on knowledge-sharing practices. On the other hand, the religiosity factor inherent in the company's human resources, results showed that the religiosity factor weakens the influence of entrepreneurial orientation on knowledge-sharing practices. The results of this study contribute empirically to testing the resource-based view (RBV) theory, where the resources owned by the company in the form of entrepreneurial orientation increase knowledge and knowledge sharing among employees. The results of this study also have implications for practical business levels, recommending that digitalization in companies will strengthen entrepreneurial orientation in encouraging knowledge-sharing practices.